Self-care management intervention for glycemic control in type 2 Diabetes Mellitus patients - Wahyuni, Sri; Prasetyowati, Christina Dewi; Pujiastutik, Yanuar Eka (Riset Informasi Kesehatan, 2025)
Background: Diabetes mellitus (DM) is a chronic condition with severe effects. Diabetes patients are advised to adopt various self-management decisions and participate in care activities to improve glycemic control. Self-care management strategies assist people with diabetes in making decisions and behaviors that improve health outcomes. Self-care management strategies can be the basis for limiting and preventing serious diabetes-related consequences and financial expenses that emerge from this disease problem. This study aims to evaluate the effect of self-care management interventions on glycemic control in people with diabetes. Method: The study was quasi-experimental, with a pre-posttest design. This study used the purposive sampling strategy with 80 participants (40 controls and 40 interventions). Data was acquired by a questionnaire from the Godin Leisure-Time Exercise Questionnaire (GLTEQ) and the UK Diabetes and Diet Questionnaire. For normal variables, paired and independent t-tests were utilized, whereas Wilcoxon and Mann-Whitney tests were applied for abnormal variables. Results: The study was quasi-experimental, with a pre-posttest design. This study used the purposive sampling strategy with 80 participants (40 controls and 40 interventions). Data was acquired by a questionnaire from the Godin Leisure-Time Exercise Questionnaire (GLTEQ) and the UK Diabetes and Diet Questionnaire. For normal variables, paired and independent t-tests were utilized, whereas Wilcoxon and Mann-Whitney tests were applied for abnormal variables. Conclusion: This study suggests that administering self-care management treatments can enhance glycemic control in diabetic patients